Clinicopathological study on camel mastitis at Matrouh Governorate (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Camel mastitis is indeed a serious problem that can have significant impacts on animal health and production as well as pose a potential public health hazard. This work aimed to identify the bacterial species responsible for camel mastitis and evaluate the associated immunological and clinicopathological alterations in infected camels. Materials and Methods: Raw milk and blood samples were collected from 40 apparently healthy she-camels, and 40 she-camels suffered from clinical mastitis (CMG). Milk samples were subjected to bacteriological examination. Serum immunological, biochemical, and hematological parameters were estimated and statistically analyzed. Results: Similar bacterial species were obtained from the two groups with different isolation rates. Staphylococcus epidermidis and Escherichia coli were the dominant species in the apparently healthy group, while Pseudomonas aeruginosa and Bacillus cereus were the dominant species in CMG. A significant (p < 0.05) elevation of the pro-inflammatory cytokines, acute phase proteins (APPs), free radicals, total protein, Glob, kidney and liver function tests, and triglyceride concentrations were detected in CMG, and a significant (p < 0.05) decrease in the anti-inflammatory cytokine, antioxidants, Alb, glucose, and T/LDL/HDL-cholesterol concentrations was observed in CMG. Microcytic hypochromic anemia with hypoferremia, hypotransferrinemia, hyperferritinemia, and neutrophilic leukocytosis was depicted in CMG. The estimated pro-inflammatory cytokines, APPs, and total antioxidant capacity (TAC) yielded high sensitivity and specificity, but the highest likelihood ratio wasfor TAC, fibrinogen (Fb), and ferritin, and the highest percentages of increase were for IL-1α and IL-1β. Conclusion: The study emphasizes the importance of hygienic preventive measures to control camel mastitis and the importance of supportive treatment to reverse the hemato-biochemical and iron profile changes that result from the immune response in mastitic she-camels. TAC, Fb, ferritin, IL-1α, and IL-1β are good biomarkers for camel mastitis.J. Adv. Vet. Anim. Res., 10(2): 284–291, July 2023http://doi.org/10.5455/javar.2023.j680